Peran Sosialisasi Pernikahan Dini dalam Membangun Kesadaran dan Mendorong Perubahan Sosial Masyarakat di Desa Bungkuk - Andhita Risko Faristiana; Dicky Wahyu Darmanto; Happy Naryana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Early marriage is a phenomenon that is often found in various regions of the world, including in Indonesia. This phenomenon presents a number of risks and negative impacts on individuals, families and society as a whole. Therefore, one of the project groups of 19 Community Service Lectures in Bungkuk Village focuses on early marriage socialization which has the aim of increasing youth awareness about the negative effects of early marriage, as well as educating them about the importance of postponing marriage until a more mature age. The method used in carrying out this work program is an Asset Based Community Development (ABCD) based approach which is based on facts and data obtained in the field. A collaborative approach involving students, lecturers, youth, and related parties is also an integral part of this program. The expected outcome of this work program is to increase the awareness of young people in Bungkuk Village about the risks of early marriage, which will eventually lead to changes in behavior and views towards postponing marriage. Through this article, it is hoped that readers will gain a deeper understanding of the significance of this community service program in overcoming the challenges of early marriage and promoting the positive development of young people.